Peran Guru Dalam Implementasi Kurikulum Merdeka Belajar Di Sd Negeri Unggulan I Kabupaten Pulau Morotai - Rawis, Joulanda A.M; Lengkong, Jeffry S.J; Hayun, Subhan; Rompis, Novie; Omkarsba, Helena; Takalumang, Luccylle (Peneliti.net, 2023)
The Free Learning Curriculum is a policy of the Ministry of Education, Culture, Research and Technology which aims to optimize the existing curriculum. The purpose of this study is to analyze teacher readiness in implementing the Merdeka Belajar Curriculum. The research method is a case study involving two teachers and a principal at the Merdeka Belajar curriculum implementing elementary school. This research was collected based on interviews, observations and documentation. Then it is analyzed through data collection, data reduction, data presentation and conclusion. The results of this study show that teacher readiness in implementing the independent learning curriculum in elementary schools is quite optimal. The obstacle factor for elementary school teachers in implementing the independent learning curriculum is the lack of understanding of the independent learning curriculum between teachers and parents. And the facilities and infrastructure are inadequate, and need support from various parties